PENINGKATAN HASIL BELAJAR SISWA KELAS VII SMP PGRI 4 MAKASSAR MELALUI PENERAPAN STRATEGI PEMBELAJARAN CROSSWORD PUZZLE - Dwiyanti Dwiyanti; Husain As (Cross-border, 2021)
This study aims to improve social studies learning outcomes through crossword puzzle learning strategies for seventh grade students of SMP PGRI 4 Makassar. This type of research is classroom action research. The subjects of this study were students of class VII SMP PGRI 4 Makassar, amounting to 15 0 people. The implementer of the action is a researcher who acts as a teacher. Methods of data collection is done through observation, tests and documentation. This classroom action research was conducted in 2 cycles, each cycle was carried out with one meeting. One cycle consists of planning, implementation, observation, and reflection stages. The results showed that the use of crossword puzzle learning strategies in social studies learning could improve the learning outcomes of seventh grade students of SMP PGRI 4 Makassar.